Motif Penggunaan Kontrasepsi Suntik 3 Bulan Pada Akseptor - Nur Saidah (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2026)
The Family Planning (FP) movement in Indonesia has become an example of how a country can respond to and embrace family planning initiatives as part of a more structured family development strategy to improve welfare in a population of approximately 259 million people. Women using Depot Medroxyprogesterone Acetate (DMPA), commonly known as the three-month injectable contraceptive, experience an average weight gain of 11 pounds (5.5 kg) and an increase in body fat of 3.4% over three years of use.The objective of this study was to identify the motives for using injectable contraceptives among family planning acceptors. This study employed a qualitative research method with a phenomenological approach, focusing on the subjective experiences of individuals. This method does not rely on numerical data or statistical principles.The findings revealed that acceptors perceived the benefits of the three-month injectable contraceptive as being easy to use, safe, practical, affordable, and not requiring frequent reminders. Support from husbands and midwives, acting as counselors, played an important role in decision-making related to seeking health services. The decision-making process and communication patterns were found to be complex. Selecting contraceptive methods that align with the preferences of married couples may enhance client satisfaction and promote more consistent contraceptive use.